Macromol. Chem. Phys. 6/2018. Issue 6 (25th March 2018) - Aiba, Motohiro; Ito, Kenji; Tokuyama, Takahiro; Tomioka, Hiroki; Higashihara, Tomoya; Ueda, Mitsuru; Matsumoto, Hidetoshi
Abstract : Front Cover : Aromatic random copolyamide membranes are prepared and characterized in article number1700522 by Hidetoshi Matsumoto and co‐workers. The partial N ‐methylation of the amide linkages suppresses hydrogen bonding between polymer chains. The size of the free volume elements can be tuned by controlling the intramolecular interaction between polymer chains, leading to improved transport properties through the membranes.